2015
DOI: 10.1016/j.parkreldis.2014.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease severity levels and MDS-Unified Parkinson's Disease Rating Scale

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 249 publications
(179 citation statements)
references
References 22 publications
4
172
1
2
Order By: Relevance
“…Here, cutoffs in each of the four parts of the scale were defined for mild, moderate or severe stages (cutoff points between mild/moderate and moderate/severe levels as follows: Part 1: 10/11 and 21/22; Part 2: 12/13 and 29/30; Part 3: 32/33 and 58/59; and Part 4: 4/5 and 12/13). This can help to better stratify disease severity of PD, identify clinical red flags for advPD and assign treatment strategies with respect to overall disease progression and with a focus on motor symptoms (Martinez-Martin et al 2015). …”
Section: Strategies To Define Diseases Stagesmentioning
confidence: 99%
“…Here, cutoffs in each of the four parts of the scale were defined for mild, moderate or severe stages (cutoff points between mild/moderate and moderate/severe levels as follows: Part 1: 10/11 and 21/22; Part 2: 12/13 and 29/30; Part 3: 32/33 and 58/59; and Part 4: 4/5 and 12/13). This can help to better stratify disease severity of PD, identify clinical red flags for advPD and assign treatment strategies with respect to overall disease progression and with a focus on motor symptoms (Martinez-Martin et al 2015). …”
Section: Strategies To Define Diseases Stagesmentioning
confidence: 99%
“…In a previous study, 6 we collected information from four global scales to determine cutoff points for assignment of primary severity levels to the scores of the Movement Disorder Society sponsored version of the Unified Parkinson’s Disease Rating Scale (MDS-UPDRS). These four scales were the Hoehn and Yahr staging (HY), 7 the Clinical Global Impression-Severity (CGIS), 1 the Patient Global Impression-Severity (PGIS), 2,8 and the Clinical Impression of Severity Index for Parkinson’s disease (CISI-PD).…”
Section: Introductionmentioning
confidence: 99%
“…After excluding patients at Hoehn and Yahr stage 3, we found that the study subjects showed a more pronounced improvement in all scores. The Hoehn and Yahr scale mostly evaluates postural instability and motor impairment, and advanced stages correlate with dopaminergic loss, motor decline, and deterioration of quality of life (15,16). Patients with advanced PD have difficulty learning skills or new tasks (17).…”
Section: Discussionmentioning
confidence: 99%